Enhanced Efficiency and Reduced Side Lobe Level Convex Conformal Reflectarray - Michele Beccaria (MDPI AG, 2021)
In this work, the design of a convex conformal reflectarray (CRA), suitable to be used for high gain on board antenna in mobile communication systems, is presented. The reflector is not planar, as in usual reflectarray configurations, but the re-radiating elements are printed on a surface conformed to a cylinder to mimic a curved surface, such as the fuselage of an airplane, on which the reflectarray could be mounted. To compensate for the loss in efficiency due to the curvature, an ad hoc feed is designed; the results obtained with the simulation of the entire structure and the measurements of its prototype prove the effectiveness of the design procedure and its capability in enhancing the CRA features, in comparison with similar but more conventional solutions.